Factors affecting visual outcome in traumatic cataract and its associated ocular injuries - A hospital based study - Ahmad Sofi, Ishfaq; Aziz, Aziz; S. Wani, Junaid (International Journal of Medical Research and Review, 2016)
Background: Ocular trauma is a major cause of visual impairment throughout the world, although little is known about the factors that affect the visual outcome in traumatic cataract in developing countries. Aims and Objectives: To find out the associated ocular injuries and the factors affecting final visual outcome of patients with traumatic cataract. Material Methods: This prospective hospital based study was conducted on 40 patients of traumatic cataract. Patients were managed with lens extraction and intraocular lens implantation. Regular follow up of patients was done and best corrected visual acuity and post operative complications were assessed at the end of six months. Results: Our study showed that majority (50%) of patients were in the age group of < 20 years with male preponderance. visual outcome was significantly better in younger age group (< 20 yrs) than the older group (> 20 yrs) ( p = 0 .03). There was no significant difference in final visual outcome of traumatic cataracts caused by penetrating or blunt trauma ( p = 0.73). Corneal tear was most common associated ocular damage followed by uveitis, lens matter in anterior chamber. Conclusions: Age of the patient affects final visual outcome after surgical treatment of traumatic cataract but type of trauma (blunt / penetrating) had no significant effect on final visual outcome. Corneal tear was most common associated ocular damage.